2023
DOI: 10.3390/jcm12020518
|View full text |Cite
|
Sign up to set email alerts
|

Three-Month Safety and Efficacy Outcomes for the Smaller-Incision New-Generation Implantable Miniature Telescope (SING IMT™)

Abstract: The smaller-incision new-generation implantable miniature telescope (SING IMT™) is the second generation of the IMT™, a telescope prosthesis that is indicated for monocular implantation in patients with stable vision impairment caused by bilateral central scotomas associated with end-stage Age-related macular degeneration (AMD). This non-comparative retrospective study is the first and largest single-surgeon case series to evaluate the short-term (3 months) safety and efficacy of the device in patients with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
(40 reference statements)
1
12
0
Order By: Relevance
“…However, sulcus implantation was not mentioned. 5 We found that the zonular stress observed during the studied rescue maneuvers was tolerable and no further, more challenging complications, such as posterior capsule rupture, arose from sulcus implantation.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…However, sulcus implantation was not mentioned. 5 We found that the zonular stress observed during the studied rescue maneuvers was tolerable and no further, more challenging complications, such as posterior capsule rupture, arose from sulcus implantation.…”
Section: Discussionmentioning
confidence: 62%
“…It is implanted through a 6.5- to 7.5-mm incision; a 5.5-mm capsulorhexis is sufficient, less sutures are needed to close the incisional wound, and the duration of the implantation procedure is greatly reduced. 5 Nevertheless, implanting the device still poses a challenge to surgeons because of its axial length of 4.4 mm, haptic diameter of 10.8 mm, its greater weight of 63 mg in the aqueous humor, the unusual unfolding action of the silicone haptics, and the delivery where the lens optic has to be aligned orthogonally to the direction of implantation (Figure 1).…”
mentioning
confidence: 99%
“…The new SING IMT shows promising characteristics, however careful study of the procedure is necessary to ensure the best outcomes. Short-term safety and efficacy results with the new SING IMT are encouraging, 6 as well as in vitro recent assessment. First of all, the cornea incision should not be performed on clear cornea in order to avoid high surgical induced astigmatism (SIA) which has been reported more than 10 Diopters in the IMT.…”
Section: Discussionmentioning
confidence: 91%
“…The new SING IMT shows promising characteristics, however careful study of the procedure is necessary to ensure the best outcomes. Short-term safety and efficacy results with the new SING IMT are encouraging, 6 as well as in vitro recent assessment. 7…”
Section: Discussionmentioning
confidence: 91%
“…We aimed at investigating safety outcomes, as well. In literature the most common reported AE were inflammatory deposits on the device [ 12 , 13 , 14 , 15 , 18 ]. Differently, we did not find any inflammatory or pigmented deposits on the lens in our study population.…”
Section: Discussionmentioning
confidence: 99%